A new genus of chevron cricket (Orthoptera: Anostostomatidae: Lutosinae) from the Colombian and Venezuelan Amazon Rainforest - de Mello Mendes, Diego Matheus; Cadena-Castañeda, Oscar J.; Heleodoro, Raphael Aquino; Ramos-Pastrana, Yardany; Rafael, José Albertino (Zootaxa, 2020)
Tintiyakus gen. nov., is described based on specimens from the Amazon region, including three species: Tintiyakus piaroa n. comb. (transferred from Hydrolutus Issa & Jaffe), Tintiyakus sexangulus sp. nov. (type-species pres. desig.) and Tintiyakus trewicki sp. nov. After Hydrolutos, this is the second anostostomatid genus described to be known from its semiaquatic behaviors, inhabiting the lowlands of the Amazon rainforest. An identification key for species based on males is provided.